2008
DOI: 10.1016/j.molcel.2008.05.025
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Estrogen Rapid Signaling through Arginine Methylation by PRMT1

Abstract: Evidence is emerging that estrogen receptor alpha (ERalpha) is central to the rapid transduction of estrogen signaling to the downstream kinase cascades; however, the mechanisms underlying this nongenomic function are not fully understood. Here we report a paradigm of ERalpha regulation through arginine methylation by PRMT1, which transiently methylates arginine 260 within the ERalpha DNA-binding domain. This methylation event is required for mediating the extranuclear function of the receptor by triggering it… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

14
220
0
6

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 264 publications
(240 citation statements)
references
References 44 publications
14
220
0
6
Order By: Relevance
“…These study findings implicate the regulation of the subcellular localization of ERα by MTA1s as a mechanism for enhancing ERα extranu-clear actions by nuclear exclusion [91]. Recent studies also found that the ERα was methylated posttranslationally, and methylated ERα was predominantly present in the cytoplasm, suggesting that deregulation of arginine methylase may have consequences in the activation of ERα extranuclear actions [61]. Collectively, these emerging results suggest that ER extranuclear signaling has the potential to affect breast cancer cell migration and metastasis.…”
Section: E2 Signaling In Breast Cancer Invasion and Metastasissupporting
confidence: 52%
See 2 more Smart Citations
“…These study findings implicate the regulation of the subcellular localization of ERα by MTA1s as a mechanism for enhancing ERα extranu-clear actions by nuclear exclusion [91]. Recent studies also found that the ERα was methylated posttranslationally, and methylated ERα was predominantly present in the cytoplasm, suggesting that deregulation of arginine methylase may have consequences in the activation of ERα extranuclear actions [61]. Collectively, these emerging results suggest that ER extranuclear signaling has the potential to affect breast cancer cell migration and metastasis.…”
Section: E2 Signaling In Breast Cancer Invasion and Metastasissupporting
confidence: 52%
“…Palmitoylation at cysteine 447 localizes ERα to the plasma membrane and is responsible for the ligand-induced activation of MAPK and PI3K/Akt pathways in breast cancer cells [60]. Another mechanism proposed is that protein arginine N-methyltransferase 1 (PRMT1) methylates ERα at argi-nine 260 in the DNA-binding domain of the ERα mediating the extranuclear function of the receptor [61]. This would then facilitate the interaction between Src/focal adhesion kinase and p85 leading to the propagation of the signal to downstream transduction cascades [61].…”
Section: E2 Signaling In Breast Carcinogenesismentioning
confidence: 99%
See 1 more Smart Citation
“…ER est méthylé par l'arginine méthyl-transférase PRMT1 sur l'arginine 260 localisée dans le domaine de liaison à l'ADN, et cette modification est essentielle à la formation d'un macrocomplexe qui contient ER/Src/PI3K/FAK (focal adhesion kinase). La méthylation de ER est rapide et transitoire, ce qui suggère l'existence d'une régulation fine de ce processus [19]. La cartographie des modifications post-traductionnelles de ER montre que ces modifications sont concentrées autour de la région charnière, ce qui laisse supposer des relations entre ces différentes modifications (Figure 2 A et B).…”
Section: Modifications Post-traductionnelles De Era Dans Les Voies D'unclassified
“…Une étude pour déterminer si la méthylation de ERpeut être considérée comme un marqueur diagnostique et/ou pronostique dans les cancers du sein est en cours [19]. Une étude réalisée sur 267 tumeurs du sein invasives a montré qu'une mutation somatique dans le gène ERa (A908G), conduisant à la substitution de la lysine 303 en arginine, est présente dans 50 % des tumeurs et est associée à un mauvais pronostic.…”
Section: Les Modifications Post-traductionnelles De Era Sont Déréguléunclassified